Haploinsufficiency of Cnot3 Aggravates Acid-Induced Acute Lung Injury Likely Through Transcriptional and Post-Transcriptional Upregulation of Pro-Inflammatory Genes - Yamaguchi T; Ozawa R; Minato T; Hoshizaki M; Kammura Y; Okawara K; Khalil YA; Nakamura M; Yamaura K; Fukuda M; Imai Y; Kuba K (Dove Medical Press, 2024)
Tomokazu Yamaguchi,1,2,* Ryo Ozawa,2,3,* Takafumi Minato,2 Midori Hoshizaki,4 Yutaro Kammura,1,5 Kazuma Okawara,1,6 Yousef A Khalil,1 Masafumi Nakamura,6 Ken Yamaura,5 Masayuki Fukuda,3 Yumiko Imai,4 Keiji Kuba1,2 1Department of Pharmacology, Kyushu University Graduate School of Medical Sciences, Fukuoka, Japan; 2Department of Biochemistry and Metabolic Science, Akita University Graduate School of Medicine, Akita, Japan; 3Department of Dentistry and Oral Surgery, Akita University Graduate School of Medicine, Akita, Japan; 4National Institutes of Biomedical Innovation, Health and Nutrition (NIBIOHN), Ibaraki, Japan; 5Department of Anesthesiology and Critical Care Medicine, Kyushu University Graduate School of Medical Sciences, Fukuoka, Japan; 6Department of Surgery and Oncology, Kyushu University Graduate School of Medical Sciences, Fukuoka, Japan*These authors contributed equally to this workCorrespondence: Keiji Kuba, Department of Pharmacology, Kyushu University Graduate School of Medical Sciences, Maidashi 3-1-1, Higashi-ku, Fukuoka, 813-0016, Japan, Email kuba.keiji.815@m.kyushu-u.ac.jpBackground: Acute lung injury (ALI) is caused by a variety of illnesses, including aspiration pneumonia and sepsis. The CCR4-NOT complex is a large multimeric protein complex that degrades mRNA through poly(A) tail shortening, whereas it also contributes to regulation of transcription and translation. Cnot3 is a scaffold component of the CCR4-NOT complex and is essential for the integrity of the complex; loss of Cnot3 leads to depletion of whole complex. While the significance of cytokine mRNA degradation in limiting inflammation has been established, the roles of CCR4-NOT complex-mediated in ALI remain elusive.Methods: The effects of Cnot3 haploinsufficiency in the pathology and cytokine expression were analyzed in the mouse lungs of acid aspiration-induced acute lung injury. The decay rate and transcription activity of cytokine mRNAs under Cnot3 heterozygous deletion were analyzed in lipopolysaccharide (LPS) -stimulated mouse embryonic fibroblasts (MEFs).Results: Tamoxifen-induced heterozygous deletion of Cnot3 in adult mice (Cnot3 Hetz) did not show body weight loss or any apparent abnormality. Under acid aspiration-induced acute lung injury, Cnot3 Hetz mice exhibited increased pulmonary edema, worse lung pathologies and more severe inflammation compared with wild type mice. mRNA expression of pro-inflammatory genes Il1b and Nos2 were significantly upregulated in the lungs of Cnot3 Hetz mice. Consistently, mRNA expression of Il1b and Nos2 was upregulated in LPS-stimulated Cnot3 Hetz MEFs. Mechanistically, while heterozygous depletion of Cnot3 stabilized both Il1b and Nos2 mRNAs, the nascent pre-mRNA level of Il1b was upregulated in Cnot3 Hetz MEFs, implicating Cnot3-mediated transcriptional repression of Il1b expression in addition to destabilization of Il1b and Nos2 mRNAs. PU.1 (Spi1) was identified as a causative transcription factor to promote Il1b expression under Cnot3 haploinsufficient conditions.Conclusion: CNOT3 plays a protective role in ALI by suppressing expression of pro-inflammatory genes Il1b and Nos2 through both post-transcriptional and transcriptional mechanisms, including mRNA stability control of Spi1.Keywords: acute lung injury, ALI, ARDS, CNOT3, CCR4-NOT complex, deadenylation